Documentation of Invasive Plant Species in Latehar and Hazaribagh Districts: Jharkhand - India - Divakara, B. N.; Prasad, Santosh; Das, Rameshwar (Indian Forester, 2013)
The survey was undertaken to document the alien invasive flora present in different ecosystems during November 2010 to February 2011 in Latehar and Hazaribagh districts of Jharkhand. A total of 41 invasive alien species was documented in the selected forests and non-forest areas. Among invasive alien species, major potential threat in the near future is by Lantana camara, Argemone mexicana, Eupatorium odoratum and Hyptis suaveolens. Lantana camara was highest in open forest with density of 2917/ha and frequency 47.62 % compared to dense forest with density of 42.5/ha and frequency 50 % in Latehar forest. Whereas in Hazaribagh forests the density of Lantana camara was higher than Latehar forests with 3535/ha in open forest and 177/ha in dense forest. In Agricultural land Celosia argentea, Argemone mexicana, Cassia tora, Eclipta prostrata, Emilia sonchifolia, Evolvulus nummularious, Oxalis corniculata, Portulaca oleracea, Scoparia dulcis, Sonchus oleraceous, and Tridax procumbens are found thorugh out Hazaribagh and Latehar districts. Eichornia cressipeswas major invasive species found in pond ecosystem.